2008
DOI: 10.1002/pros.20738
|View full text |Cite
|
Sign up to set email alerts
|

Functional angiotensin II type 2 receptors inhibit growth factor signaling in LNCaP and PC3 prostate cancer cell lines

Abstract: Functional AT(2)-receptors are present and have the capacity to inhibit EGF-induced prostate cancer cell growth in LNCaP and fast growing androgen-independent PC3 cell lines, whereas functional AT(1)-receptors are found only in LNCaP cells where their activation stimulates DNA synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 24 publications
1
44
0
Order By: Relevance
“…With regard to the prostate, there is clear evidence of a tissue-based renin-angiotensin system within this gland and studies to date indicate beneficial actions of blocking AT1R and activating AT2R (15,(20)(21)(22)(23). For example, AT1R inhibitors decrease the growth of some prostate cancer cell lines and delay the development of prostate cancer, whereas AT2R inhibitors are present and have the ability to inhibit epidermal growth factor-induced prostate cancer cell growth in LNCaP and fast-growing androgen-independent PC3 cell lines (24). Increased expression of AT2R induces apoptosis in numerous cell lines, such as pheochromocytoma, fibroblasts, smooth muscle cells, and endothelial cells, with either Ang II-dependent or Ang II-independent regulation (25)(26)(27)(28)(29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the prostate, there is clear evidence of a tissue-based renin-angiotensin system within this gland and studies to date indicate beneficial actions of blocking AT1R and activating AT2R (15,(20)(21)(22)(23). For example, AT1R inhibitors decrease the growth of some prostate cancer cell lines and delay the development of prostate cancer, whereas AT2R inhibitors are present and have the ability to inhibit epidermal growth factor-induced prostate cancer cell growth in LNCaP and fast-growing androgen-independent PC3 cell lines (24). Increased expression of AT2R induces apoptosis in numerous cell lines, such as pheochromocytoma, fibroblasts, smooth muscle cells, and endothelial cells, with either Ang II-dependent or Ang II-independent regulation (25)(26)(27)(28)(29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that neoplastic cells derived from prostate epithelial cells generally show an increased expression of both ATIP isomers and the results are consistent with our results in human malignancies (Table 1). The reason for low ATIP1 mRNA levels in PC3 cells is uncertain but this cell line also demonstrates low levels of functional AT 1 -receptors [2,4] and it is tempting to speculate that the two findings are related.…”
Section: Resultsmentioning
confidence: 99%
“…Our earlier in vitro studies clearly indicate that in spite of the presence of relatively low levels of AT 2 -receptor mRNA, activation of the AT 2 -receptor significantly inhibited EGF-induced LNCaP and PC3 cell growth [2]; in the absence of AT 2 -receptor activation, ATIP mRNA expression decreased when the cells were stimulated with EGF [10]; and that AT 2 -receptor activation inhibited the EGF-induced down-regulation of ATIP mRNA. These studies, in combination with the work described previously in this section, indicate that EGF may stimulate prostatic cell growth, at least in part, by reducing the levels of ATIP present in the cells and that activation of the AT 2 -receptor may prevent this down-regulation from occurring, thus suggesting that an important interaction exists between ATIP and the AT 2 -receptor in mediating prostate cancer cell growth.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental and clinical studies clearly showed that sunitinib mainly acts by inhibiting VEGFR2 activation on endothelial cells [21] which triggers a negative feedback in tumours leading to a VEGF-A oversecretion [24]. Moreover, AT1-R blockers have been described to inhibit VEGF-A secretion by tumour cells [25] and decrease tumor angiogenesis [22, 26] as well as tumour cell proliferation [27]. AT1-R antagonists could also trigger cancer cell apoptosis [28].…”
Section: Discussionmentioning
confidence: 99%